2020
DOI: 10.18814/epiiugs/2020/020053
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of active gas hydrate mounds in the southwestern slope of the Chukchi Plateau, Arctic Ocean

Abstract: This study documents the discovery of mound morphologies containing gas hydrate and methane-derived authigenic carbonate (MDAC) in the southwestern slope of the Chukchi Plateau, during the IBRV Araon expeditions in 2016 and 2018. A multibeam bathymetric surveying was the basis for a new and detailed rendering around the mounds. Sub-bottom profiles and site-targeted gravity cores were also collected across these mounds which were located at water depths between 780 m and 580 m. Mounds are characterized by a cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…Доступные результаты исследований δ 13 C (CH 4 ), проведенные по сипам газа в морях Восточной Арк тики вдали от современного положения речных дельт, практически повсеместно показали его глубинный генезис [31; 38; 46]. При этом в Чукотском бассейне δ 13 C (CH 4 ) изменялся от -63,6‰ до -55,6‰ [38], что близко к данным по метану биогенного генезиса с глубин 500-1300 м сеноманских отложений севера Западной Сибири [3; 4]. В абсолютном большинстве исследований [31] в море Лаптевых в придонных осадках и сипах был обнаружен термогенный метан с δ 13 C (CH 4 ) от -43‰ до -37‰, а также более тяжелые молекулярные соединения (этан, пропан и др.).…”
Section: анализ температур воды вблизи дна моряunclassified
“…Доступные результаты исследований δ 13 C (CH 4 ), проведенные по сипам газа в морях Восточной Арк тики вдали от современного положения речных дельт, практически повсеместно показали его глубинный генезис [31; 38; 46]. При этом в Чукотском бассейне δ 13 C (CH 4 ) изменялся от -63,6‰ до -55,6‰ [38], что близко к данным по метану биогенного генезиса с глубин 500-1300 м сеноманских отложений севера Западной Сибири [3; 4]. В абсолютном большинстве исследований [31] в море Лаптевых в придонных осадках и сипах был обнаружен термогенный метан с δ 13 C (CH 4 ) от -43‰ до -37‰, а также более тяжелые молекулярные соединения (этан, пропан и др.).…”
Section: анализ температур воды вблизи дна моряunclassified
“…The M07 is underlain by continuous thick sediment and a smooth basement (Hegewald, 2012;Hegewald & Jokat, 2013) which is a sedimentary environment that facilitates reliable heat flow measurements (Sclater et al, 1976). Site ARA09C01HFP from Kim et al (2020) is located ∼70 km south of M07 and its thermal gradient (56.5 mK/m) is similar to that of M07, although the associated conductivity has not been published yet.…”
Section: Heat Flow Distributionsmentioning
confidence: 99%
“…The stars and hexagons indicate the heat flow sites from O' Regan et al (2016) and the global heat flow database (IHFC, 2012), respectively. The eight sites at roughly 81°N (Jokat, 2009) and one site in the Chukchi Abyssal Plain (Kim et al, 2020) without thermal conductivity are indicated by small octagons. The bathymetry contour interval is 1,000 m. AR, Alpha Ridge; CAA, Canadian Arctic Archipelago; CAP, Chukchi Abyssal Plain; CB, Canada Basin; CP, Chukchi Plateau; EI, Ellesmere Islands; FJ, Franz Josef Island; HT, Hanna Trough; KPR, Knipovich Ridge; LR, Lomonosov Ridge; MB, Makarov Basin; MR, Mendeleev Ridge; NCB, North Chukchi Basin; NCBL, Northern Chukchi Borderland; NSI, New Siberia Island; NWB, Northwind Basin; NWR, Northwind Ridge.…”
mentioning
confidence: 99%
“…Gas venting from shelf sediments has been attributed to the dissociation of gas hydrates in paleopermafrost [35][36][37][38]. The relation of methane venting from bottom sediments with gas hydrates on the Russian Arctic shelf has received no direct proof though, in the absence of test boreholes [39,40], but it was recently reported regarding the continental slope of the Russian Arctic in Chukchi Sea [41], and from other Arctic areas (Spitsbergen, Beaufort Sea, etc.) [42,43].…”
Section: Introductionmentioning
confidence: 99%